Physical Health Screenings Among African-American Church and Community Members - Moore, Erin W. (Journal of religion and health, 2016)
This study sought to identify characteristics, including religiosity, related to having received health screenings among persons who attend African-American churches or receive church-based community outreach services. A sample of 602 was recruited during two phases as part of a larger project. Blood pressure, cholesterol, and blood glucose screenings were the most frequently reported screenings ever and in the last 12 months. Although religiosity was significantly related to several of the health screenings in bivariate analysis, it is not a predictor of health screenings in multivariate analyses. Innovative strategies are needed to promote screenings such as church-based health fairs.